Preparation And Characterization Of Electrospun Ceramic Nanofibers Into Polyimide Composite Films - Meng, Sopheak (2017)
Recently, many researchers have focused on one-dimensional materials such as nanofibers to enhance dielectric properties of the composites due to the unique properties. In this study, polyimide/ceramic nanofibers composite films were prepared by incorporating various types of ceramic nanofibers (BaTiO3, TiO2 and ZrO2) to polyimide matrix derived from 2,2-Bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 3,3',4,4'-Biphenyl tetracarboxylic dianhydride (BPDA). The ceramic nanofibers were prepared by the combination of sol-gel process, electrospinning and calcination before incorporating with polyimide via in-situ polymerization assisted by ultrasonication. Fourier transform infrared (FTIR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), impedance analyzer (LCR meter), Differential Scanning calorimetry (DSC) and thermal gravimetric analysis (TGA) were used to characterize properties of composite films such as chemical structure, crystal phase, morphology, dielectric and thermal properties. FTIR spectra showed the characteristic peaks of the imide groups in the composite films as well as absorption bands corresponding to ceramic nanofibers. XRD diffractograms demonstrated the composite films exhibited the crystal structure similar to those of their parent ceramic nanofibers. The results from SEM micrographs indicated ceramic nanofibers were well dispersed in the composite films due to their large aspect ratio and ultrasonication method. Dielectric constant of the PI/BaTiO3 (20 wt%) is 6.78 (about 2 times of pure polyimide) with low dielectric loss of 0.009 at 1 MHz and room temperature. Lastly, all of the composite films also showed high thermal stability.